MiR-196b-5p activates NF-κB signaling in non-small cell lung cancer by directly targeting NFKBIA - Wangyu Zhu; Yun Yu; Yuxin Ye; Xinyue Tu; Yan Zhang; Tao Wu; Lianli Ni; Xiangjie Huang; Yumin Wang; Ri Cui (Translational Oncology, 2023)
Background: Our recent study found that QKI-5 regulated miRNA, miR-196b-5p, promotes non-small cell lung cancer (NSCLC) progression by directly targeting GATA6, TSPAN12 and FAS. However, the biological functions of miR-196b-5p in NSCLC progression and metastasis still remain elusive. Methods: Cell proliferation, migration, colony formation, cell cycle assays were used to investigate cellular phenotypic changes. Quantitative real-time PCR (qRT-PCR) and western blot analyses were used to measure expressions of relative gene and protein. Interaction between QKI-5 and miR-196b-5p was determined by RNA immunoprecipitation (RIP) assay. Luciferase reporter assay was used to determine direct binding between miR-196b-5p and NFKBIA 3′-UTR. ELISA assay was used to measure secreted IL6 proteins. Mice xenograft model was used to assess the functions of NFKBIA on in vivo tumor growth. Results: We demonstrated that the miR-196b-5p facilitates lung cancer cell proliferation, migration, colony formation, and cell cycle by directly targeting NFKBIA, a negative regulator of NFκB signaling. Knocking down NFKBIA increases IL6 mediated phosphorylation of signal transducer and activator of transcription 3 (STAT3) to promote lung cancer cell growth by activating NFκB signaling. The expression of NFKBIA was significantly downregulated in NSCLC tissue samples, and was negatively correlated with the expression miR-196b-5p. In addition, we found that downregulated QKI-5 expression was associated with the elevated miR-224 expression in NSCLC. Conclusions: Our findings indicated that the miR-224/QKI-5/miR-196b-5p/NFKBIA signaling pathway might play important functions in the progression of NSCLC, and suggested that targeting this pathway might be an effective therapeutic strategy in treating NSCLC.